WEAVING ACTIVITIES IN EARLY CHILDREN TO IMPROVE THE FINE MOTORIC OF GROUP B CHILDREN TK ABA MEDAN - Pohan, Selamat (Proceeding International Seminar of Islamic Studies, 2023)
Regarding improving the quality of fine motor skills in Early Childhood, teachers must have high creativity in conveying learning by using activities that make children highly motivated and enthusiastic about learning. One of them is with weaving activities which have the aim of improving the fine motor skills of early childhood. This study uses qualitative methods and is descriptive in nature with data collection techniques by observation, interviews, documentation and triangulation of sources. The subjects of this study consisted of 19 students in group B. The purpose of this study was to determine the fine motor development of children through weaving activities in the form of mats and mangoes in TK ABA Medan. The results of the study show that children's fine motor development can develop through this weaving activity. Even though they still need guidance and direction from the teacher and the teacher. After this research was carried out, it was necessary to have an intensity of in-depth follow-up teaching for the motor development of children in the TK. One of them is by using weaving activities and not only with the teacher's diary, but adding other activities.